The Influence Of Hit Distances And Dimensions Candlenut For Perfomance Improvement On Breaking Machine Candlenut - Anggara, Mietra; Ardiansyah (International Journal of Science, Technology & Management, 2021)
Candlenut is one of the crops that grow in Indonesia. In Batu Dulang village Batulante sub-district Sumbawa there are candlenut entrepreneurs whose process of breaking candlenut seeds is still manual, person can break 14 – 17 kg/day of candlenut. This reseach was aimed to examine the influence of distance and dimension of candlenut and to increase the performance machines at nutcracker . This reseach was conducted in November to December 2020 at workshop engineering study program, faculty of technique, Sumbawa university. The method used was a case study striking distance (18 mm, 20 mm, 22 mm) small Candlenut dimensions, 18mm to 25 mm, large Candlenut dimension 26 mm to 35 mm, with three levels of treatment and each treatment combination was striking distance of dimensions three time. The parameters of this study ware the parcentage of the whole core, parcentage of split halves, parcentage of core broken and parcentage of seeds escaped. The results of this study indicate that the treatment striking distance of dimensions has a significant effect on percentage of crushed core and percentage of seeds escaped. The highest of the intact core wa found at a small Candlenut dimensions striking distance 18 mm 60%, parcentage of split halves of 18 mm 20%, parcentage of 20 mm 10% core broken and parcentage of 22 mm 60% seeds escaped. The highest of the intact core wa found at a larges Candlenut dimensions striking distance 20 mm 53,33% parcentage of split halves of 18 mm yaitu 30% parcentage of 18 mm 10%,core broken and parcentage of 22 mm 60% seeds escaped.